Assessing the Effects of Indigenous Migration on Zootherapeutic Practices in the Semiarid Region of Brazil - Santos, Carlos Alberto Batista (PLoS One, 2016)
Human migration implies adaptations to new environments, such as ways to benefit from the available biodiversity. This study focused on the use of animal-derived remedies, and we investigated the effects of migration on the traditional medical system of the indigenous Truká people. This ethnic group lives in Northeast Brazil and is currently distributed in four distinct villages. In these villages, the zootherapeutic knowledge of 54 indigenous people was determined through semi-structured questionnaires given from September 2013 to January 2014. The interviewees indicated 137 zootherapeutic uses involving 21 animal species. The variety of species and their uses have a higher similarity between villages that are closer to each other, which can be a reflection of geographic and environmental factors. However, even close villages showed a low similarity in the zootherapeutic uses recorded, which reflects a strong idiosyncrasy regarding the knowledge of each village. Hence, each village may be influenced by the physical environment and contact with other cultures, which may maintain or reduce the contact of younger villages with the original village.